2022
DOI: 10.1021/acs.jafc.2c05719
|View full text |Cite
|
Sign up to set email alerts
|

Bta-miR-493 Inhibits Bovine Preadipocytes Differentiation by Targeting BMPR1A via the TGFβ/BMP and p38MAPK Signaling Pathways

Abstract: Fat deposition significantly impacts the meat yield and the meat quality of beef cattle, which is closely associated with the preadipocyte proliferation and differentiation. Bta-miR-493 is expressed differentially in the backfat of Qinchuan cattle of various ages, and it may be involved in the fat accumulation of beef cattle. However, the role and functional mechanism of bta-miR-493 in fat deposition are still unclear. Tissue-specific expression analysis showed that the level of bta-miR-493 was moderately abun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Similarly, Huang et al reported that the knockdown of SMAD4 disrupts the BMP2/4-induced adipogenic commitment process in the same cellular model . Long et al demonstrated that inhibition of upstream components, such as BMPR1 promotes preadipocyte proliferation but inhibits their differentiation in a culture of bovine preadipocytes …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Huang et al reported that the knockdown of SMAD4 disrupts the BMP2/4-induced adipogenic commitment process in the same cellular model . Long et al demonstrated that inhibition of upstream components, such as BMPR1 promotes preadipocyte proliferation but inhibits their differentiation in a culture of bovine preadipocytes …”
Section: Resultsmentioning
confidence: 99%
“… 41 Long et al demonstrated that inhibition of upstream components, such as BMPR1 promotes preadipocyte proliferation but inhibits their differentiation in a culture of bovine preadipocytes. 42 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the low IMF content of yak meat has become a major bottleneck, restricting high-quality meat development in the yak industry. Recent studies report that non-coding RNAs (ncRNAs) regulate key aspects of lipid metabolism [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%